Effects of humic acid-based cation buffer on chemical characteristics of saline soil and growth of maize - W Mindari; N Aini; Z Kusuma; S Syekhfani (Brawijaya University, 2014)
Humic acid is believed to maintain the stability of the soil reaction, adsorption / fixation / cationic chelate, thereby increasing the availability of water and plant nutrients. On the other hand, the dynamics of saline soil cation is strongly influenced by the change of seasons that disrupt water and nutrient uptake of plants. This experiment was aimed to examine the characteristics of the humic acid from compost, coal, and peat and its function in the adsorption of cations (K+ and NH4+), thus increasing the availability of nutrients and growth of maize. The treatments tested were combination of three sources of humic acid (compost, peat and coal), two types of cation additives (K+ and NH4+), and three doses of humic acid-based buffer: 10, 20, and 30 g / 3kg. The treatments were evaluated against changes in pH, EC, cation exchange, chlorophyll content, plant dry weight and plant height. The experimental results showed that the addition of K+ and NH4+ affected the value of pH, CEC, K+, NH4+ and water content of the buffer. Application of humic acid-based buffer significantly affected exchangeable Na and exchangeable K. Humic pH dropped from > 7 to about 6.3, EC soil was about 0.9 mS / cm, exchangeable Ca, exchangeable Mg, exchangeable Na, and exchangeable K, respectively, were around 15.57-20:21; 1.76-6.52; 0.40-0.56 and 0.05-0.51 me / 100g soil. Plant growth (plant height, chlorophyll content, leaf area, and stem weight) at 35 days after planting increased with increasing dose of humic acid. The dose of 20g peat humic acid + NH4+ or 30g peat humic acid + K+ per 3 kg of saline soil gave the best results compared to the growth of maize from other treatments.